2009
DOI: 10.1007/s10562-009-0112-y
|View full text |Cite
|
Sign up to set email alerts
|

Etidronic Acid: a New and Efficient Catalyst for the Synthesis of Novel 5-Nitro-3,4-Dihydropyrimidin-2(1H)-Ones

Abstract: A simple, convenient and efficient one-pot cyclocondensation reaction of 1-(2-hydroxyphenyl)-2-nitroethanone, arylaldehydes and urea using etidronic acid to furnish nitro dihydropyrimidine derivatives is described. A new and efficient protocol is developed as a homogenous catalyst for the synthesis of dihydropyrimidines using substituted x-nitro acetophenone. Various bisphosphonic acids were examined to synthesized pyrimidines via multicomponent cyclocondensation reaction. This methodology has the advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Various organocatalysts such as tartaric acid, oxalic acid, citric acid, and lactic acid were found effective in producing Biginelli products [164][165][166][167][168][169][170][171][172]. Because of the "privileged" green nature of this field, it has become an obligation for scientific community and academic institutions to be mindful and teach this branch of catalysis to students and also keep it as a driving force in the generation and dissemination of knowledge in pursuit of efficient synthetic methodologies and processes using organocatalysts.…”
Section: Other Amino Acidsmentioning
confidence: 99%
“…Various organocatalysts such as tartaric acid, oxalic acid, citric acid, and lactic acid were found effective in producing Biginelli products [164][165][166][167][168][169][170][171][172]. Because of the "privileged" green nature of this field, it has become an obligation for scientific community and academic institutions to be mindful and teach this branch of catalysis to students and also keep it as a driving force in the generation and dissemination of knowledge in pursuit of efficient synthetic methodologies and processes using organocatalysts.…”
Section: Other Amino Acidsmentioning
confidence: 99%
“…An efficient approach to the green synthesis of glycoluryls in an aqueous medium using P 4 O 10 as a catalyst, under mild conditions with the possibility of recycling both solvent and catalyst, is reported in Ref. [39] More recently, in a number of works [40][41][42] it was found that etidronic acid (HEDP) proved to be a convenient "green" catalyst in 3-component reactions of the formation of dihydropyrimidones using carbonyl compounds with an active methylene group, urea and aldehydes as under traditional conditions, [40,41] and under microwave synthesis. [42] However, examples of the use of HEDP as a catalyst in the reactions of 1, 2-dicarbonyl compounds with ureas are still not known.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work we synthesized nitro dihydropyrimidine derivatives via multi‐component reaction in the continuation to this, we were interested in the synthesis of 1 H ‐imidazo[1,2‐ b ]pyrazoles derivatives catalyzed by Etidronic acid as a green catalyst which are easily accessible. The title compounds were prepared via multicomponent GBB reaction in one pot sequential steps by the condensation of 5‐amino‐1 H ‐pyrazole, aldehyde and isocyanide.…”
Section: Introductionmentioning
confidence: 99%